Integration of ethnoscience in problem-based learning to improve contextuality and meaning of biology learning - Suciyati, Alfi; Suryadarma, I Gusti Putu; Paidi, Paidi (Universitas Negeri Jakarta, 2021)
Meaningful learning can be carried out by adapting learning to local culture and traditions. Ethnoscience is a set of knowledge identified in a community and can be used as the learning base to create contextual and meaningful learning for students. This study aims to find more information about ethnoscience-based biology learning. The research method used was a literature study. The literature used mainly discusses ethnoscience, ethnoscience learning, and learning methods. The instrument used in this study was a summary table of all related articles, following the summary table made by Cronin et al. (2008). This research produces a new conceptual framework which is a synergy between ethnoscience and problem-based learning. This research also generates six procedures for designing ethnoscience-based learning and five steps to integrate ethnoscience into Problem-based Learning. The integration of ethnoscience in problem-based learning can increase the contextuality and meaning of biology learning and can be applied to maintain local culture. This study recommends the use of procedures resulted from this study to design ethnoscience-based learning and integrate ethnoscience learning into Problem-Based Learning.